Fuel consumption and CO2 emission investigation of range extender with diesel and gasoline engine - Wahono, Bambang; Nur, Arifin; Praptijanto, Achmad; Santoso, Widodo Budi; Suherman, Suherman; Lu, Zong (Journal of Mechatronics, Electrical Power and Vehicular Technology, 2016)
Range extender engine is one of the main components of the range-extended electric vehicle (REEV) and together with a generator to extend the mileage of the electric vehicle. The main component of REEV is an electric motor, battery, and generator set that consist of generator and engine. In this study, we compared two models of REEV performance with two different types of the engine by simulation. Single cylinder 499 cc gasoline engine and single cylinder 667 cc diesel engine are chosen as the object of this research especially relating to the utilization of the fuel consumption and CO2 emissions when fitted to an electric vehicle. The simulation was conducted by using AVL Cruise software and performed by entering the data, both experiment and simulation data, on all the main components of REEV. This simulation was performed in Japan 08 driving cycle. Based on the simulation, fuel consumption is reduced up to 35.59% for REEV with single cylinder diesel engine 667 cc compared to REEV with single cylinder gasoline engine 499 cc. The reduction of CO2 emissions from REEV with single cylinder 499 cc gasoline engine compared to REEV with single cylinder 667 cc diesel engine up to 30.47%.